FREE LEGAL AID IN THE CONTEXT OF THE RIGHT OF ACCESS TO COURT - Čanović, Jelena; Palačković, Dušica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The Constitution of the Republic of Serbia explicitly regulates that free legal aid shall be stipulated by law. In a series of reports on the progress of the Republic of Serbia in the process of joining the EU there are warnings about the unacceptably low level of quality and efficiency of the judiciary, and in this context indications that there is necessity for regulation of the free legal aid system by law. Finally, this matter is stipulated with law which came into force as of October 1st, 2019. In addition to the conceptual definition of free legal aid, the paper analyzes the conditionality of the right to access to court as a constituent element of the right to a fair trial proscribed with the Article 6 of European Convention on Human Rights, by exercising the right to free legal aid. Regulation of free legal aid at the national level has to meet the standards formulated at the level of the European Union as well as standards formulated through the practice of the European Court of Human Rights, so the paper analyzes the reference regulations and decisions, i.e. standards that are recognized and accepted. The Law on Free Legal Aid of the Republic of Serbia has been analyzed in the context of meeting of standards, especially in relation to the conditions for granting the right to free legal aid and the circle of beneficiaries and providers of certain types of free legal aid.